Kepemimpinan Inovatif dalam Dunia Pendidikan, Analisis Peran Nadiem Makarim dalam Transformasi Pendidikan Indonesia - Widya Oktarina; Viola Desmita; Febrian Mukharromah; Yulia Hanoselina; Rizky Syafril (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Education is a conscious and planned effort to develop a person's potential as a whole. In this context, leadership plays an important role in creating an education system that is adaptive and responsive to the needs of the times. This study aims to analyze the innovative leadership style of Nadiem Makarim in his role as Minister of Education and Culture of the Republic of Indonesia through a literature study approach. Nadiem, previously known as the CEO of Gojek, brings a new paradigm to the world of education by emphasizing the importance of flexibility, creativity, and the use of technology. Through the Merdeka Belajar policy, he seeks to eliminate bureaucracy that hinders innovation and build a learning system that is oriented towards real competencies. This study highlights how Nadiem forms a personal branding as a leader who dares to make breakthroughs and how he influences the culture and direction of educational transformation in Indonesia. This study uses a literature analysis method or literature study, namely by collecting various sources of literature ranging from books to journals that are coherent with the research topic.